Handbook of Sustainability Science and Research (World Sustainability Series, 2018)
This multidisciplinary handbook explores concrete case studies which illustrate how sustainability science and research can contribute to the realization of the goals of the 2030 Agenda for Sustainable Development. It contains contributions from sustainability researchers from across the world.